DIRECT VERBAL VERBS IN THE LETTERS OF SORROWS BY AL-RAFI’I: A PRAGMATIC STUDY - Zaman Ali Hassan; Qusay Ibrahim Nimah Al-Hussuna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The speaker to communicate his intention to the listener takes different expressive methods and methods, as the nature of the deliberative dimension seeks to comprehensively encompass all the pillars of the creative process from the speaker and the listener, given that pragmatics is the science in which language is studied within various discursive contexts according to linguistic mechanisms based on the nature of the recipient and the situation. Al-Khatabi and the circumstances surrounding it, the study came as a contemporary linguistic study of the book Letters of Sorrows by Al-Rafei, in which he finds the most important purposes and objectives of his speech.